Evaluation of immediate reactions to β lactam antibiotics using a comprehensive diagnostic protocol - Bhagwat, Bhanuja; H. V., Anuradha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: β lactam antibiotics are commonly prescribed groups of antibacterial drugs for various infections however the prevalence of its allergic effects is not clear in our country, hence the need for an effective diagnostic protocol to determine immediate hypersensitivity reactions. The objective was to formulate a diagnostic protocol for evaluating immediate drug hypersensitivity to β lactam antibiotics. Methods: A prospective study was conducted at a tertiary care hospital. Adults who were prescribed any class of β lactam antibiotic were included. Non irritating concentrations of the antibiotic as per The European Network on drug Allergy were used. A strict three step diagnostic algorithm with skin prick test followed by intradermal test and drug provocation test, with 20 minutes observation period between each step, to determine cutaneous allergic reactions was followed. Results: The most commonly prescribed drug was cefazolin, followed by ceftriaxone, and cefoperazone + sulbactam combination. The culprit drugs were ceftriaxone in 4 (4.7%) patients, followed by piperacillin + tazobactam combination in 3 (3.5%), amoxicillin + clavulanic acid in 2 (2.3%) and 1 (1.1%) each for cefotaxime and cefepime + tazobactam combination. No patients were positive for skin prick test; 2.4% were positive for intradermal test and 10.6% were positive for drug provocation test. Conclusions: This diagnostic protocol is apt to adequately diagnose immediate reactions to β lactam antibiotics and henceforth can be used effectively in India. However, the skin prick test may be excluded but the intradermal test and drug provocation test is crucial to identify these immediate reactions.